Ecological risk assessment of heavy metals in Morus alba leaves in Rafsanjan and Sarcheshmeh, the southeast area of Iran - Eslami, Hadi; Ebrahimi, Ensieh; Baberi, Faezeh; Fallahzadeh, Reza Ali (Spatial information research (Online), 2024)
This study aimed to assess the ecological risks of heavy metals in Morus alba leaves in Rafsanjan and Sarcheshmeh, southeast area of Iran, in 2022. Morus alba leaves were collected from the trees surrounding the streets in 14 sampling stations. Heavy metals including As, Cr, Cu, Ni, Pb, Zn, and Mn, and other metals including Al, S, P, Na, K, Mg, and Fe were determined via inductively coupled plasma-mass spectrometry (ICP-MS). Risk Index (RI) was used to assess the ecological risk potential. The concentration of heavy metals was found in the following order: Zn > Cu > Mn > Cr > Ni > Pb > As as well as Mg > K > P > S > Fe > Al for the other metals. The concentration of Cr, Cu, Ni, Mn, and Pb was higher in the samples from Sarcheshmeh compared to Rafsanjan. The highest ecological risk (E r i ) was 12.67-101.56 for As, which was in the range of considerable risk, with RI in the range of 40.37-187.32. The ecological risk and RI for Pb in Rafsanjan and Sarcheshmeh were in the range of low and moderate risk, respectively. Thus, heavy metals assessment in the industrial areas by Morus alba leaves is recommended.